Peran Artificial Intelligence dalam Meningkatkan Efisiensi Administrasi dan Kualitas Pelayanan Rumah Sakit: Systematic Literature Review - Ardiansyah Ahmad; Destriyana Indah Damayanti; Raharjani Puspita Ludiana; Latifah Dwi Andini; Emilda Yuliasari; Siti Rohana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
The use of Artificial Intelligence (AI) in hospital management continues to grow to support information management, improve operational efficiency, and enhance service quality. This study aimed to analyze the areas of hospital management that most frequently utilize AI, its contribution to administrative efficiency, its impact on service quality, and the challenges associated with its implementation. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Articles were retrieved from Google Scholar, Garuda, and PubMed between 2022 and 2026. Of the 172 articles identified, 25 met the inclusion criteria and were included in the analysis. The results showed that AI is primarily applied in electronic medical records, clinical and managerial decision support systems, human resource management, logistics and pharmacy management, and telemedicine services. AI helps accelerate administrative processes, reduce repetitive workloads, improve data accuracy, enhance diagnostic accuracy, increase service responsiveness, and improve patient satisfaction. However, its implementation still faces challenges, including limited digital infrastructure, inadequate human resource competencies, regulatory issues, data security concerns, and budget constraints. AI has the potential to become a strategic solution for improving administrative efficiency and healthcare service quality when supported by adequate infrastructure, skilled personnel, appropriate regulations, and effective data governance.